INTEGRATION OF INTERNET MEMES WHEN TEACHING PHILOLOGICAL DISCIPLINES IN HIGHER EDUCATION INSTITUTIONS - Anna Kyrpa; Olena Stepanenko; Viktoriia Zinchenko; Hannah Udovichenko; Liliia Dmytruk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2022)
A rapid increase of available information affects students' perception of any message and formation of priorities; the period of concentration on one subject is reduced; students prefer concise vivid visual images. Internet memes become a part of students' daily communication and broadcast today's cultural and information realities. The aim of the study was to evaluate the effectiveness of Internet memes integration while mastering philological disciplines (for example, English) by Ukrainian students. The authors experimented to check the methodology proposed within one program unit. We conducted the experiment in the 2020-2021 academic year and involved 68 students and 5 teachers of Dnipro Academy of Continuing Education, Donetsk State University of Internal Affairs and Mykhailo Tuhan-Baranovskyi Donetsk National University of Economics and Trade. The authors conducted pre- and post-experimental surveys and informal interviews to compare academic achievements and provided a system of tasks integrating memes. Implementing the experiment, we clarified the dominant way of students' perception and processing of information and revealed the expediency of integrating memes into teaching English. The authors determined the dynamics of the levels of students' motivation to learn English through Internet memes integration and established quantitative values of the levels using the method of mathematical statistics. The conclusions emphasize the need to improve teachers' pedagogical skills, developed critical and creative thinking to integrate memes into educational activities. The authors stress the relevance of the further detailed study of the educational potential of memes in teaching not only philological disciplines but also other subjects of the curriculum.